Are We Experiencing a Decolonial Turn on Brazilian Scientific Education? (Revista Brasileira de Pesquisa em Educação em Ciências, 2023)
In roughly seventy years of existence in Brazil, research in science teaching has shifted its theoretical and methodological frameworks. As an effect of these changes, over the decades there have been some booms in publications focusing on new research approaches in this area. Glancing at Brazilian scientific till mid-2021, we suggest the emergence of another wave in the sea of science education, attracted by discussions associated with the impacts of colonization on education. In this work, we first present part of the polyphonic theorization related to resistance to colonization and highlight relevant points of this dialogue for our area. Later, based on bibliographical research, we show the increase in the number of articles related to these perspectives published in national journals by the science teaching community. In addition, we brought events that probably contributed to catalyze the income of this theoretical framework into the area in Brazil. We raised the hypothesis that the year of 2004 was the starting point of the introduction of decolonial framework in Brazilian science education and the year of 2019 as the turning point for anchoring a crucial movement for the promotion of social justice in science teaching in the country.